Expression of genes encoding extracellular matrix macromolecules and metalloproteinases in avian tibial dyschondroplasia - Velada, I (2011)
Avian tibial dyschondroplasia (TD) is a skeletal disease characterized by disruption of endochondral bone formation. The aim of this study was to determine the expression of extracellular matrix (ECM) macromolecules and ECM-degrading enzymes [matrix metalloproteinases (MMPs)] in the growth plates of normal and TD-affected 3-week-old broiler chicks (Cobb strain). Protein levels were analyzed by immunoblotting and gelatin zymography and gene expression by polymerase chain reaction. Expression of genes encoding the ECM macromolecules (collagen types II, IX, X and XI; and aggrecan) was not altered in dyschondroplasia; however, there was down-regulation of genes encoding MMP-9, MMP-13, MMP-10 and MMP-11 in addition to reduced amounts of MMP-2 and MMP-13 proteins. In contrast, there was up-regulation of genes encoding MMP-7 and the vascular endothelial growth factor. These findings suggest that the accumulation of cartilage associated with the disease may be the result of decreased proteolysis due to the down-regulation of MMPs and not to an increased production of ECM macromolecules.